Analisis Yuridis Asas Final dan Mengikat dalam Putusan Arbitrase Nasional di Indonesia - Endah Trihandayani; Rudi Natamiharja; Sepriyadi Adhan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The final and binding principle is a fundamental principle in arbitration that grants arbitral awards permanent legal force and binds the parties without the availability of ordinary legal remedies. This study aims to analyze the regulation and implementation of the final and binding principle in national arbitral awards in Indonesia. The research employs a normative juridical method through the examination of statutory regulations and related legal documents. The results indicate that the final and binding principle provides legal certainty and supports dispute resolution in a fast and effective manner. However, its implementation remains limited by the mechanism for annulment of arbitral awards and the principle of public policy.